1989
DOI: 10.1016/0014-5793(89)81539-x
|View full text |Cite
|
Sign up to set email alerts
|

Raison d'être and structural model for the B‐Z transition of poly d(G‐C)poly d(G‐C)

Abstract: In DNA oligonucleotides crystallized in the A form, the nucleotides adopt standard conformation except for steps 5'‐CpG‐3' where reduced base‐pair twist and a sliding motion of the base pairs along their long axes causes pronounced interstrand guanine‐guanine overlap. As a consequence, torsion angles α,β and γ are consistently trans, trans, trans instead of the common ‐gauche, trans, + gauche. This conformation significantly increases the intraresidue distance between the guanine base and the 5'‐phosphate grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
25
0

Year Published

1992
1992
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 35 publications
1
25
0
Order By: Relevance
“…A number of molecular mechanisms have been proposed for the B-Z transition. [31] There is no spectroscopic support for intermediates in three models, the Saenger-Heinemann model, [32] the stretched model, [33] and the zipper model, [34] probably owing to the short lifetime of the intermediates. Goto et al successfully observed an intermediate, designated as B Ã -DNA, in the B-Z transition induced under high salt conditions using a stopped-flow apparatus.…”
Section: Discussionmentioning
confidence: 99%
“…A number of molecular mechanisms have been proposed for the B-Z transition. [31] There is no spectroscopic support for intermediates in three models, the Saenger-Heinemann model, [32] the stretched model, [33] and the zipper model, [34] probably owing to the short lifetime of the intermediates. Goto et al successfully observed an intermediate, designated as B Ã -DNA, in the B-Z transition induced under high salt conditions using a stopped-flow apparatus.…”
Section: Discussionmentioning
confidence: 99%
“…A number of molecular mechanisms have been proposed to explain the change in the handedness of DNA double helix and the 180°base-pair plane rotation during the B-Z transition, including the Wang model, 1 the Harvey model, 12 the A-DNAlike intermediate model, 13 and the model based on the crystal structure of a B-Z junction. 14 The Wang model proposes that base-pair opening occurs before base-pair plane and phosphate backbone angle rotation.…”
Section: Introductionmentioning
confidence: 99%
“…A third hypothesis assumes a transition through an intermediate (A-type) conformation without disruption of Watson-Crick hydrogen bonds and without sterical interference (50,51).…”
Section: Introductionmentioning
confidence: 99%